Isaiah in context : studies in honour of Arie van der Kooij on the occasion of his sixty-fifth birthday - Kooij, Arie van der, 1945-; Meer, Michaël N. van der.; Keulen, P. S. F. van.; Peursen, W. Th. van.; Haar Romeny, R. B. ter. (Vetus Testamentum, Supplements, 2010)
The present volume contains a collection of essays on the Book of Isaiah offered as a tribute to Arie van der Kooij on the occasion of his sixty-fifth birthday, which coincides with his retirement as Professor of Old Testament at Leiden University. The twenty-four contributions, written by leading scholars in the field of Old Testament studies, focus on the Book of Isaiah within the context of Hebrew and ancient near-eastern writings, particularly those from the Neo-Assyrian period, as well as on the book's reception history , particularly in its Greek and Syriac translations. Together these studies offer a rich and original contribution to the study of the Book of Isaiah in its Hebrew, Aramaic, Assyrian, Greek, Syriac, and Dutch contexts.